Essential elements of treatment and care in high secure forensic inpatient services: an expert consensus study. Issue 3 (8th August 2016) - Tapp, James; Warren, Fiona; Fife-Schaw, Chris; Perkins, Derek; Moore, Estelle
Abstract : Purpose: – The evidence base for what works with forensic patients in high-security inpatient settings has typically focused on outcome research and not included clinical expertise from practice-based experience, which is an important facet of evidence-based practice. The purpose of this paper is to establish whether experts with clinical and/or research experience in this setting could reach consensus on elements of high-security hospital services that would be essential to the rehabilitation of forensic patients. Design/methodology/approach: – A three-round Delphi survey was conducted to achieve this aim. Experts were invited to rate agreement with elements of practice and interventions derived from existing research evidence and patient perspectives on what worked. Experts were also invited to propose elements of hospital treatment based on their individual knowledge and experience. Findings: – In the first round 54 experts reached consensus on 27 (out of 39) elements that included physical (e.g. use of CCTV), procedural (e.g. managing restricted items) and relational practices (e.g. promoting therapeutic alliances), and to a lesser extent-specific medical, psychological and social interventions. In total, 16 additional elements were also proposed by experts. In round 2 experts ( n =45) were unable to reach a consensus on how essential each of the described practices were. In round 3 ( n =35), where group consensus feedback from round 2 was provided, consensus was still not reached. Research limitations/implications: – Patient case complexity, interventions with overlapping outcomes and a chequered evidence base history for this population are offered as explanations for this finding alongside limitations with the Delphi method. Practical implications: – Based on the consensus for essential elements derived from research evidence and patient experience, high-secure hospital services might consider those practices and interventions that experts agreed were therapeutic options for reducing risk of offending, improving interpersonal skills and therapeutic interactions with patients, and mental health restoration. Originality/value: – The study triangulates what works research evidence from this type of forensic setting and is the first to use a Delphi survey in an attempt to collate this information.